Epistemology, Learning, and Self-Development among Immigrant Women of Color: The Case of the British Caribbean Women in the United States - Mary V. Alfred (Adult Education Research Conference, 2001)
This study examined how British Caribbean women construct knowledge from their transcultural experiences and how they use their acquired knowledge to facilitate their learning and development. The women have endured the challenges of their cross cultural transitions because they learned how to work, how to learn, how to overcome silence and marginality, and how to negotiate their way through the American cultural systems.